Correct Answer - Option 3 : -1

**Formula used :**

sin(90° - θ) = cosθ

cos(90° - θ) = sinθ

cosec(90° - θ) = secθ

tan2θ - sec2θ = -1

**Calculations :**

sin(80° + θ) + cos(65° + θ) - cos(10° - θ) + tan2θ - cosec2(90° - θ) - sin(25° - θ)

⇒ sin(80° + θ) - cos(10° - θ) + cos(65° + θ) - sin(25° - θ) + tan2θ - cosec2(90° - θ)

⇒ sin(80° + θ) - sin(90° - (10° - θ) + cos(65° + θ) - cos(90° - (25° - θ) + tan2θ - cosec2(90° - θ).

⇒ sin(80° + θ) - sin(80° + θ) + cos(65° + θ) - cos(65° + θ) + tan2θ - sec2θ

⇒ 0 + 0 + (-1)

⇒ -1

**∴ Option 3 is the correct choice **